ANALISIS DEFORMASI LATERAL GRUP PONDASI TIANG DENGAN PERKUATAN MENGGUNAKAN TIANG MIRING (BATTER PILES) PADA JEMBATAN DERMAGA - Hidayat, Wirman (Jurnal Ilmiah Teknik Sipil; Jurnal Ilmiah Teknik Sipil, Vol. 25, No. 1, Januari 2021, 2021)
ABSTRACT: Lateral deformation of group piles foundation is one of the parameters that must be considered properly, excessive lateral deformation can cause damage to the structure. In bridge structures, cases of excessive lateral deformation often occur which potentially affect the reliability of the bridge and cause damage to the structure. When the lateral deformation that occurs in the foundation group exceeds the safety limit, it needs additional reinforcement designed to provide additional lateral resistance, so that the deformation that occurs can be reduced and the strength of the structure also increases. Reinforcement using inclined piles (batter piles) can be used in increasing the lateral resistance of the group piles foundation. The use of batter piles mechanically distributes the horizontal load to the vertical direction of the foundation, so that the lateral load that carried by the foundation is distributed into vertical and horizontal components, to reduce the lateral deformation that occurs. In this study, the lateral deformation analysis was carried out on the group piles foundation on the jetty bridge which experienced a large deformation, then a reinforcement design was designed using batter piles to increase lateral resistance. The analysis was performed using PLAXIS 2D and GROUP software. From the analysis, it was found that reinforcement using batter piles can reduce the lateral deformation that occurs and increase the stability of the bridge.. Keywords: batter piles, lateral deformation, lateral resistance